2021
DOI: 10.4314/jopat.v19i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic and physicochemical evaluation, HPLC analysis and antiproliferative properties of Kigelia africana (Lam.) Benth

Abstract: Introduction/Objective of study: Kigelia africana (Bignoniaceae) is enriched with bioactive constituents and has thus found various uses in African folklore. This study aims to evaluate the pharmacognostic, physicochemical, chromatographic and antiproliferative properties of K. africana.Methodology: Standard methods were used to determine the qualitative microscopy, moisture content, ash and extractive value. Furthermore, HPLC analysis was conducted on the samples in order to detect and quantify some phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…(2014) and Fatokun et al . (2019); which reported a high similarity with the terpene profile found in this study. Quantification of the total terpenes amounted 1997.05 ± 263.35 mg/100 g DW, highlighting the high presence of hydrocarbon monoterpenes (95.7%) followed far behind by oxygenated monoterpenes (4.0%).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…(2014) and Fatokun et al . (2019); which reported a high similarity with the terpene profile found in this study. Quantification of the total terpenes amounted 1997.05 ± 263.35 mg/100 g DW, highlighting the high presence of hydrocarbon monoterpenes (95.7%) followed far behind by oxygenated monoterpenes (4.0%).…”
Section: Resultssupporting
confidence: 83%
“…The identification of a-terpinene, p-cymene, limonene, terpinolene, thymol, carvacrol and ascaridole coincides with that reported by Harraz et al (2014) and Fatokun et al (2019); which reported a high similarity with the terpene profile found in this study. Quantification of the total terpenes amounted 1997.05 AE 263.35 mg/100 g DW, highlighting the high presence of hydrocarbon monoterpenes (95.7%) followed far behind by oxygenated monoterpenes (4.0%).…”
Section: Identification and Quantification Of Terpenes By Gc-mssupporting
confidence: 91%
See 1 more Smart Citation
“…It is a hairy, strongly aromatic, annual, or short-lived perennial herb that usually grows wild in Central and South America (Soares et al, 2017). The stem of the plant is equipped with glandular trichomes that secrete essential oils (Fatokun et al, 2019). According to Soares et al (2017), it is traditionally used as a flavoring agent in various kinds of dishes due to its pungent flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Each cluster of flowers usually has 3-5 sepals, partially or united, with 3-5 stamens, free or with adnate filaments, on each sepal. It also has numerous, spherical, black colored seeds that are surrounded by a persistent calyx that is less than 0.8 mm long (Fatokun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%